Inequalities in antenatal care coverage and quality: an analysis from 63 low and middle-income countries using the ANCq content-qualified coverage indicator - Luisa Arroyave; Ghada E. Saad; Cesar G. Victora; Aluisio J. D. Barros (BMC, 2021)
Abstract Background Antenatal care (ANC) is an essential intervention associated with a reduction of maternal and new-born morbidity and mortality. However, evidence suggested substantial inequalities in maternal and child health, mainly in low- and middle-income countries (LMICs). We aimed to conduct a global analysis of socioeconomic inequalities in ANC using national surveys from LMICs. Methods ANC was measured using the ANCq, a novel content-qualified ANC coverage indicator, created and validated using national surveys, based upon contact with the health services and content of care received. We performed stratified analysis to explore the socioeconomic inequalities in ANCq. We also estimated the slope index of inequality, which measures the difference in coverage along the wealth spectrum. Results We analyzed 63 national surveys carried out from 2010 to 2017. There were large inequalities between and within countries. Higher ANCq scores were observed among women living in urban areas, with secondary or more level of education, belonging to wealthier families and with higher empowerment in nearly all countries. Countries with higher ANCq mean presented lower inequalities; while countries with average ANCq scores presented wide range of inequality, with some managing to achieve very low inequality. Conclusions Despite all efforts in ANC programs, important inequalities in coverage and quality of ANC services persist. If maternal and child mortality Sustainable Development Goals are to be achieved, those gaps we documented must be bridged.